2019
DOI: 10.1111/jch.13689
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure response to treatment of obese vs non‐obese adults with sleep apnea

Abstract: Many patients with obstructive sleep apnea (OSA), but not all, have a reduction in blood pressure (BP) with positive airway pressure (PAP) treatment. Our objective was to determine whether the BP response following PAP treatment is related to obesity. A total of 188 adults with OSA underwent 24‐hour BP monitoring and 24‐hour urinary norepinephrine collection at baseline. Obesity was assessed by waist circumference, body mass index, and abdominal visceral fat volume. Participants adherent to PAP treatment were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Research procedures were conducted and data was processed at each site individually. Some findings from site 2 have been previously reported [ 30 ].…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…Research procedures were conducted and data was processed at each site individually. Some findings from site 2 have been previously reported [ 30 ].…”
Section: Methodsmentioning
confidence: 59%
“…The primary goal was to compare the effects of PAP therapy on cardiovascular risk measures between obese and lean patients with OSA. Information on the study was previously published [ 30 ] (ClinicalTrial.gov NCT01578031). Study subjects from University of Pennsylvania were included in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…47 Obesity and obstructive sleep apnea are both risk factors for resistant hypertension, but a study that looked at the effect of CPAP therapy on blood pressure in patients with obesity vs those without obesity found no significant difference between the groups. 48 Given the high prevalence of obstructive sleep apnea in those with resistant hypertension, screening for it should be common in this population. Screening tools such as the STOP-BANG score can help risk-stratify patients who have suggestive symptoms and who should be tested with polysomnography, the gold standard for diagnosis.…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%
“…17 Although obesity is a risk factor for OSA and an independent risk factor for HTN, the influence of obesity on BP response to CPAP OSA. 18 This consecutive multicenter study included 188 OSA patients with AHI ≥ 15, which were divided into two groups: obese The results indicate that obesity was not the factor that influenced BP response to treatment of adults with OSA and that BP response to CPAP treatment was not related to baseline 24-hour urinary norepinephrine or change in 24-hour urinary norepinephrine after treatment. Several previous studies reported that change in sympathetic nervous activity, measured by plasma or urinary catecholamine levels, did not correlate with the BP response to CPAP treatment.…”
mentioning
confidence: 92%
“…In this issue of the Journal, Kuna et al assessed the BP response to CPAP treatment in obese and non‐obese adults with OSA . This consecutive multicenter study included 188 OSA patients with AHI ≥ 15, which were divided into two groups: obese and non‐obese subjects.…”
mentioning
confidence: 99%